Dualism of Foundation Governance and Its Legal Implications: A Legal Analysis of Court Decision No. 6/Pdt.G/2025/PN Agm on Civil Wrongdoing - Puspita, Dela; Mayasari, Riri Tri; Putra, Hendi Sastra; Ardinata, Mikho (Fakultas Syariah INSURI Ponorogo, 2025)
Disputes over foundation governance in Indonesia are frequently resolved through formal administrative approaches, often overlooking the substantive legitimacy of founders and internal procedures. This study analyzes judicial reasoning in Court Decision No. 6/Pdt.G/2025/PN Agm, specifically regarding the validity of management and its alignment with the principle of legality. Utilizing normative legal methods, including statutory, conceptual, and case approaches, this research examines court decisions, legislation, and academic literature. The findings suggest that the court prioritizes administrative aspects over statutory requirements, including founders' meetings and articles of association. This leads to non-normative reasoning, including the pragmatic assumption that